Aplikasi Perhitungan Pajak Impor (Studi Kasus Di Istana Grosir Group) - Ivonila Anggraeni; Agung Wahana; Iwan Sidharta (Jurnal Computech & Bisnis (e-Journal), 2017)
The development of information technology should be utilized positively for the better development of life. In relation to the obligation to the State, in this case is import tax, it is necessary to utilize the progress of information technology. One form of utilization of information technology is to create applications that can facilitate the calculation of import tax. For this reason this research is made so that in the calculation of import tax can facilitate business actors. The results of import tax calculation application in general can help companies in calculating import tax.  Keywords: application of import tax calculation.